Inovasi Produk Cassava Japanese Cheesecake Terhadap Uji Organoleptik: Product Innovation of Cassava Japanese Cheesecake Based on Organoleptic Testing - Otje Herman Wibowo; Irra Chrisyanti Dewi; Fabiola Leoparjo; Hari Minantyo; Ham Sylvia Cindy Hartono; Patricia Alberta; Jeanette Magdalene Pekanto; Devi Ramadhani Hariyono (Universitas Djuanda, 2026)
This study aims to develop a gluten-free Japanese cheesecake by substituting wheat flour with boiled cassava (Manihot esculenta Crantz) as a local food ingredient. The growing demand for gluten-free bakery products and Indonesia’s dependence on imported wheat flour encourage the utilization of cassava as an alternative raw material. This research employed a descriptive quantitative approach using three formulations: 100% wheat flour, 50% wheat flour–50% cassava, and 100% cassava. Organoleptic tests were conducted with 90 respondents to evaluate taste, aroma, texture, color, and overall appearance using a five-point hedonic scale. The results indicated that cassava-based Japanese cheesecake was well accepted by respondents, with the 100% cassava formulation obtaining the highest preference score. The substitution of wheat flour with cassava did not significantly alter the characteristic soft, moist, and fluffy texture of Japanese cheesecake. This product innovation demonstrates that cassava can be effectively utilized as a gluten-free alternative ingredient while increasing the economic value of local commodities and offering a healthier dessert option for consumers with gluten intolerance.